One fearful yellow eye - MacDonald, John D. (John Dann), 1916-1986 (MacDonald, John D. (John Dann), 1916-1986. Travis McGee series., 2013)
Travis McGee arrives in Chicago to investigate the theft of thousands of dollars during Glory Doyle's husband's last painful year, and comes across a particularly sadistic blackmailer--Novelist.